2019
DOI: 10.1111/pcmr.12840
|View full text |Cite
|
Sign up to set email alerts
|

The exocyst is required for melanin exocytosis from melanocytes and transfer to keratinocytes

Abstract: Skin pigmentation involves the production of the pigment melanin by melanocytes, in melanosomes and subsequent transfer to keratinocytes. Within keratinocytes, melanin polarizes to the apical perinuclear region to form a protective cap, shielding the DNA from ultraviolet radiation‐induced damage. Previously, we found evidence to support the exocytosis by melanocytes of the melanin core, termed melanocore, followed by endo/phagocytosis by keratinocytes as a main form of transfer, with Rab11b playing a key role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 22 publications
9
38
0
Order By: Relevance
“…Rab11A and Rab17 are involved in the melanosome transfer step presumably by promoting filopodium formation and membrane shedding (Beaumont et al., 2011; Koike et al., 2019b) (Figure 2, box 5‐ii). By contrast, Rab11B regulates melanosome exocytosis, that is, direct fusion between the melanosome limiting membrane and the plasma membrane, through interaction with exocyst component Sec8 (Moreiras et al., 2020; Tarafder et al., 2014) (Figure 2, box 5‐iii). Validation of the transfer models and identification of the precise molecular mechanism of the melanosome transfer await further investigation.…”
Section: Rab Gtpases In Melanosome Transfer From Melanocytic Dendritementioning
confidence: 99%
“…Rab11A and Rab17 are involved in the melanosome transfer step presumably by promoting filopodium formation and membrane shedding (Beaumont et al., 2011; Koike et al., 2019b) (Figure 2, box 5‐ii). By contrast, Rab11B regulates melanosome exocytosis, that is, direct fusion between the melanosome limiting membrane and the plasma membrane, through interaction with exocyst component Sec8 (Moreiras et al., 2020; Tarafder et al., 2014) (Figure 2, box 5‐iii). Validation of the transfer models and identification of the precise molecular mechanism of the melanosome transfer await further investigation.…”
Section: Rab Gtpases In Melanosome Transfer From Melanocytic Dendritementioning
confidence: 99%
“…Recent studies revealed that small GTPase Rab11 is involved in the release of melanocytes from melanocytes by exocytosis. Rab11B induces exocytosis through remodeling of the mature melanosomal membrane [59,60]. Exocytosis is initiated by the interaction between Rab11 and tethering factors, which are composed of eight subunits including Sec8, Sec15, and Exo70.…”
Section: Tlr2 and Melanocyte Functionsmentioning
confidence: 99%
“…Exocytosis is initiated by the interaction between Rab11 and tethering factors, which are composed of eight subunits including Sec8, Sec15, and Exo70. Rab11 and the tethering factors anchor melanosome vesicles to the plasma membrane [60]. Rab11A is structurally very similar to Rab11B and interacts with Sec15 in mammals [54,61].…”
Section: Tlr2 and Melanocyte Functionsmentioning
confidence: 99%
“…Sec15 is part of the exocyst complex, implicated in the tethering of secretory vesicles to the plasma membrane (Heider and Munson, 2013) and exocytosis of recycling endosomes (Takahashi et al, 2012). Recently, our group also demonstrated that the exocyst complex, together with Rab11b, is required for melanosome exocytosis (Moreiras et al, 2019). Surprisingly, in HeLa cells, the silencing of other exocyst subunits does not affect lysosome exocytosis, suggesting that the role of Sec15 in lysosome exocytosis is independent of the exocyst complex.…”
Section: Discussionmentioning
confidence: 98%